Tissue engineering strategies for treating intervertebral disc degeneration - Nie, Guangshuai; Liu, Weiyang; Zeng, Fanjia; Hu, Jia; Wang, Zhen; Huang, Zhonglian; Chen, Hongjiang; Hu, Jun; Xu, Jiankun (Frontiers in Bioengineering and Biotechnology, 2025)
Low back pain (LBP) is becoming prevalent in clinics, owing primarily to intervertebral disc degeneration (IDD). The mechanism of IDD is complex, and its pathophysiology is primarily characterized by a decrease in intervertebral nucleus pulposus cells and an imbalance in the synthesis and degradation of the extracellular matrix of the intervertebral disc (IVD). Grounded in the concept of regenerative repair, IVD engineering has emerged as a significant research focus in spinal surgery. This review systematically examines the relationship between LBP and IDD, describes the physiological characteristics of healthy IVD and the pathological features of IDD (including inflammatory responses and stress stimulation), and provides an overview of current treatment methods and clinical trials. The review focuses on summarizing and evaluating tissue engineering research, particularly the preclinical and clinical findings on the effects of various seed cells, bio-scaffolds, and bioactive factors on IVD, to explore a more comprehensive therapeutic approach. Lastly, the obstacles and opportunities of tissue engineering repair of the IVD are highlighted.